2011
DOI: 10.15835/nsb346336
|View full text |Cite
|
Sign up to set email alerts
|

Genes of Microorganisms: Paving Way to Tailor Next Generation Fungal Disease Resistant Crop Plants

Abstract: The automation of sequencing technologies, flooding in the knowledge of plant-pathogen interactions and advancements in bioinformatics provide tools leading to better knowledge not only of the genome of plant pathogens or microorganism beneficial to plants but also of ways of incorporating genes from microbes into plants as microbial-derived resistance. The identification of various microorganism genes playing key role during pathogensis and the dissection of the signal transduction components of the hypersens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…It has been observed in several reports that Trichoderma spp. inhibits the growth of various soil-borne pathogens by secreting chitinases (Rai et al 2016a;Almeida et al 2007;Kashyap et al 2011), β-glucanases (Haran et al 1995), and proteinases (Geremia et al 1993) enzymes. Similarly in the current study, Trichoderma and Hypocrea isolates displayed significant biological control activity toward R. solani on both dual plate confrontation as well as volatile metabolite assays; however, a noticeable decline was observed in their antagonistic activity as salt concentration increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed in several reports that Trichoderma spp. inhibits the growth of various soil-borne pathogens by secreting chitinases (Rai et al 2016a;Almeida et al 2007;Kashyap et al 2011), β-glucanases (Haran et al 1995), and proteinases (Geremia et al 1993) enzymes. Similarly in the current study, Trichoderma and Hypocrea isolates displayed significant biological control activity toward R. solani on both dual plate confrontation as well as volatile metabolite assays; however, a noticeable decline was observed in their antagonistic activity as salt concentration increased.…”
Section: Discussionmentioning
confidence: 99%
“…The vertical bars indicate the standard error of three replications and different letters on the error bars indicate significant difference (p < 0.05) analyzed by DMRT under saline environment. Several reports indicated that plant growth promotion by these isolates display augmentation of defense-related plant enzymes viz., β-1,3-glucanases, chitinases peroxidases, and phenylalanine peroxidases (Rawat et al 2013;Solanki et al 2011;Harman 2006;Kashyap et al 2011). Alternations in plant metabolism trigger accretion of antimicrobial compounds (such as phytoalexin and phenolics) to offer durable resistance against distinct types of abiotic and biotic stresses (Mohiddin et al 2010;Heydari and Pessarakli 2010;Shoresh et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Plant biotechnologists also showed great interest in protecting vulnerable plant varieties by activating their defense responses (Table 1). While the inhibition of virulence factors is also under intense investigation, avirulence genes (Avr) in plant pathogens and their corresponding resistance genes (receptors) in the host plants have received considerable attention in the past two decades, because the products of resistance genes may directly or indirectly serve as receptors for pathogen Avr factors [33,34]. Plants express resistance by activating appropriate signal transduction pathways, in which elicitors are the primary messengers (product of Avr) that interact with the products of the corresponding genes (receptors), thereby activating plant defense mechanisms.…”
Section: Microbial Transgenes In Plants and Pathogen Resistancementioning
confidence: 99%
“…Plants express resistance by activating appropriate signal transduction pathways, in which elicitors are the primary messengers (product of Avr) that interact with the products of the corresponding genes (receptors), thereby activating plant defense mechanisms. Elicitors are mostly encoded by pathogens themselves, while in some cases, pathogens hydrolyze the plant cell wall, and the hydrolyzed components work as elicitors or primary messengers in signal transduction [34,35].…”
Section: Microbial Transgenes In Plants and Pathogen Resistancementioning
confidence: 99%
See 1 more Smart Citation